2017
DOI: 10.1177/1357633x16686777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of telehealth intervention on breast cancer patients’ quality of life and psychological outcomes: A meta-analysis

Abstract: Introduction Telehealth intervention has been proposed as an innovative intervention approach to breast cancer patients, but there are still conflicting results in the literature about its effect. Methods PubMed, EMBASE, CENTRAL and China National Knowledge Infrastructure (CNKI) were searched from inception to 3 October 2016 for randomized controlled trials (RCTs) which assessed the effect of telehealth intervention versus usual care in breast cancer patients. No language restrictions were used. Standardized m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(141 citation statements)
references
References 32 publications
8
129
1
3
Order By: Relevance
“…Grouping the studies by delivery and duration of interventions did not resolve heterogeneity. Chen et al () reported similar failure on reducing heterogeneity in groups through dividing the studies by delivery and duration of interventions. Similarly, Soon‐Rim and Myung Kyung () reported that control condition might be one of the heterogeneity resources and the e‐health interventions had stronger effects when the controls were designed as usual care or waiting list.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Grouping the studies by delivery and duration of interventions did not resolve heterogeneity. Chen et al () reported similar failure on reducing heterogeneity in groups through dividing the studies by delivery and duration of interventions. Similarly, Soon‐Rim and Myung Kyung () reported that control condition might be one of the heterogeneity resources and the e‐health interventions had stronger effects when the controls were designed as usual care or waiting list.…”
Section: Discussionmentioning
confidence: 95%
“…Some meta‐analyses integrated the overall effect of e‐health interventions (Chen, Guan, Li, & Li, ; Seiler, Klaas, Troster, & Fagundes, ; Soon‐Rim & Myung Kyung, ; Zhang et al, ). However, Soon‐Rim and Myung Kyung () and Zhang et al () focused on telecare, which consisted of a series of medical services, such as interview, health education, and follow‐up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other research has suggested a possible improvement in QoL using telehealth in patients with breast cancer. 26 Ensuring that high-quality care is maintained through telehealth is also important. The processes of care and surrogate measures for ESRD included in our review varied across studies, ranging from complication control, dialysis adequacy (Kt/V), consultation time, and adherence to scheduled dialysis sessions.…”
Section: Commentary On Findings: Implications and Applicationsmentioning
confidence: 99%
“…Telehealth interventions reduce the need for travel and can improve access to specialist services, and hence decrease disparities in healthcare access (World Health Organization, 2016). Videoconferencing interventions have been found to be beneficial and convenient for the broader cancer population (Cox et al, 2017), and the efficacy of telehealth interventions for improving QoL and psychological outcomes after breast cancer has been demonstrated relative to usual care (see meta-analysis by Chen, Guan, Li, & Li, 2018). However, the efficacy of telehealth interventions for delivering psychosocial support has not been systematically evaluated for the brain tumour population.…”
Section: Introductionmentioning
confidence: 99%